Spectral domain optical coherence tomography predictors of visual outcome in diabetic cystoid macular edema after bevacizumab injection - Al Faran, Abdulrahman (2014)
Purpose: To study prognostic spectral domain optical coherence tomography parameters in diabetic cystoid macular edema after anti–vascular endothelial growth factor therapy. Methods: Retrospective cohort study included 49 eyes with the new onset diabetic cystoid macular edema that had to have a macular spectral domain optical coherence tomography and fluorescein angiography at presentation. The baseline optical coherence tomography scans were analyzed for variables indicative of the extent of retinal involvement by the cystoid change and its location about the center. Univariate and multivariate analyses were performed comparing the optical coherence tomography findings between the two groups of eyes: the “No improvement” and the “Improvement” groups, based on at least two Snellen lines improvement after treatment. Results: There were 30 and 19 eyes in the No improvement and Improvement groups, respectively. In the univariate analysis, the baseline optical coherence tomography parameters associated with visual improvement included the photoreceptor inner segments thickness centrally (P = 0.009) and within the central 1-mm subfield (P < 0.0001), and the presence of bridging retinal processes centrally (P = 0.004). Multivariate analysis showed both presence and central location of bridging retinal processes within the central 1-mm subfield to be significantly associated with visual improvement (P = 0.041 and 0.005, respectively), with an odds ratio of 13.4 (95% confidence interval, 1.336–636.18; P = 0.010) for their central location. Conclusion: In diabetic cystoid macular edema, visual improvement after anti–vascular endothelial growth factor therapy is more likely to occur in eyes with residual central retinal processes on baseline macular spectral domain optical coherence tomography. This finding may be helpful in patient counseling, case selection, and clinical trial planning.